Strategi Komunikasi Kreatif Produksi Take Me Out Indonesia Dalam Mempertahankan Rating - Fatnurrahman, Muhammad Afif; Hariyati, Farida; yuliani, Magvira; Solihin, Olih (Universitas Komputer Indonesia, 2024)
Take Me Out Indonesia is a reality TV show that brings together people who are looking for life partners. The format of the show involves several stages of introduction and challenges designed to help participants showcase their personalities and interests. The objective of this study is to analyze the strategies devised by the creative team of Take Me Out Indonesia to maintain its ratings. This study employs a qualitative approach with data collection techniques through interviews. The results of this study indicate that the production process of